An Unusual Cause of Intestinal Ulcers Masquerading as Inflammatory Bowel Disease: A Case Report of Allied Disorders of Hirschsprung’s Disease - Hu M; Fang H; Hu Y; Lu C; Chen Y; Zhong Z; Shi H; Wang Q (Dove Medical Press, 2024)
Minli Hu,1,* Hao Fang,2,* Yibing Hu,1 Chong Lu,1 Yuan Chen,1 Zhifeng Zhong,3 Hongqi Shi,4 Qunying Wang1 1Department of Gastroenterology, Jinhua Municipal Central Hospital, Jinhua, Zhejiang, People's Republic of China; 2Department of Traumatology, Jinhua Municipal Central Hospital, Jinhua, Zhejiang, People's Republic of China; 3Department of Anus & Intestine Surgery, Jinhua Municipal Central Hospital, Jinhua, Zhejiang, People's Republic of China; 4Department of Pathology, Jinhua Municipal Central Hospital, Jinhua, Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Qunying Wang, Department of Gastroenterology, Jinhua Municipal Central Hospital, Jinhua, Zhejiang, People's Republic of China, Email wqy616717@126.comBackground: Allied disorders of Hirschsprung's disease (ADHD) exhibit symptoms akin to those of Hirschsprung's disease, primarily characterized by intestinal obstruction, bowel dilatation, and chronic constipation. The occurrence of amyloid complications in patients with ADHD is infrequent. In this report, we present a case of ADHD with intestinal ulcers as the initial gastrointestinal manifestation, and subsequent pathological examination revealed the presence of amyloid deposits in the colonic mucosa.Case Report: A male patient, aged 20, exhibited recurring abdominal distension and intestinal obstruction for a duration of three years. Multiple colonoscopies revealed the presence of recurrent colonic ulcers, with pathological examination indicating the existence of amyloid deposits within the mucosal layer of the colon. Abdominal CT scans suggested colonic dilatation. Following a multidisciplinary consultation, a subtotal resection of the colon was performed, and subsequent postoperative pathology confirmed a decrease and absence of myenteric plexus ganglion cells. Considering the patient's symptoms and the findings from the postoperative pathology, a diagnosis of ADHD was made. The patient's symptoms resolved postoperatively and he was discharged from the hospital and followed up for 1 year in stable condition.Conclusion: Our study highlights the potential association between ADHD and the initial presentation of recurrent colonic ulcers, accompanied by amyloid deposition in the intestinal mucosa. This finding suggests a possible pathogenic mechanism for ADHD and offers a novel perspective on its diagnosis.Keywords: allied disorders of Hirschsprung's disease, colonic ulcer, amyloid, intestinal obstruction, colonoscopy biopsy colonic